Secularism, Assimilation and the Crisis of Multiculturalism - Jansen, Yolande (Taylor & Francis, 2025)
This remarkable study develops a theoretical critique of contemporary discourses on secularism and assimilation, arguing that the perspective of assimilating distinct religious minorities by incorporating them into a secular and supposedly neutral public sphere may be self-subverting. To flesh out this insight, Jansen draws on the paradoxes of assimilation as experienced by the French Jews in the late 19th century through a contextualised reading of Proust's In Search of Lost Time. She proposes a dynamic, critical multiculturalism as an alternative to discourses focusing on secularism, assimilation and integration.